A systematic design methodology of PD fuzzy logic controller using cellular fuzzy logic concept. (4th February 2013) - Das Sharma, Kaushik
The present paper proposes a new approach for designing PD type fuzzy controllers, which employs the idea of fuzzy input space partitioning using the cellular fuzzy logic (CFL) framework, deploying the dynamical behaviour of the system to be controlled. The objective is to design PD type fuzzy controllers, determining both its structures and free parameters, such that the designed controller can provide satisfactory transient performance. A novel algorithm is presented to design the generalised proportional derivative fuzzy logic controller (PD-FLC). The proposed design methodology is detailed for the synthesis of both the Mamdani type and Takagi-Sugeno (T-S) type fuzzy controller equivalent to a PD control action. The validity of the design procedure is demonstrated by simulation case studies.